Estimation green space in Yogyakarta City in the year of 2002-2019 using NDVI approach - Fitria Nucifera; Cornelius Deni Wijaya Putra; Sakinatul Afidah; Sola Tri Astuti (Universitas Negeri Yogyakarta, 2020)
Increasing the number of population which then has an impact on increasing the growth of land use change that will reduce the area of vegetation inevitable for urban areas, one of them is the City of Yogyakarta. Measurement of the availability of green space in this study utilizes remote sensing technology with NDVI analysis. The purpose of this study was to determine the estimated density of green space constituents and spatial distribution patterns of potential green space locations in the city of Yogyakarta using Landsat 7 ETM + satellite imagery data for 2002 and Landsat 8 OLI in 2019 with the Normalized Difference Vegetation Index (NDVI) method. Based on the Minister of Public Works Regulation on Guidelines for Provision and Utilization of Green Open Space in Urban Areas (05 / PRT / M / 2008), it explains that the proportion of green open space in urban areas is at least 30%. But from 2002 to 2019, Yogyakarta City which has an area of 32.84 km² was only able to meet the proportion of green space by 13.50% for 2002 and 10.53% for 2019. Then for 17 years Yogyakarta City has not met the minimum standard of green open space proportions.